Effectiveness of group-based psycho-education on preventing postpartum depression among pregnant women by primary healthcare provider in primary healthcare institution: a cluster-randomized controlled trial - Tessema, Marta; Abera, Muluemebet; Birhanu, Zewdie (Frontiers in Psychiatry, 2024)
Background In Ethiopia, one in five mothers suffers from postpartum depression, which needs to be prevented through interventions. According to the World Health Organization, maternal healthcare providers have a unique opportunity to provide psychosocial interventions to prevent the damaging effects of perinatal depression. Hence, this study assessed the effectiveness of prenatal group-based psycho-education in preventing postpartum depression (PPD) in primary healthcare units. Methods We conducted a two-arm cluster-randomized controlled trial, enrolling 550 pregnant women at 12–20 weeks of gestation with a normal score (0–4) and a mild score (5–9) on the Patient Health Questionnaire-9 (PHQ-9). The study utilized simple randomization techniques to assign clusters between arms in a 1:1 ratio. The data was collected through face-to-face interviews conducted at 12-20 weeks of gestation and 6 weeks postpartum. The intervention group received usual care plus five prenatal group-based psycho-education (PGBPE) classes, while the control group received only usual care. The PPD status between arms was compared using the chi-square test of association. A mixed-effects multilevel logistic regression model was also used to examine the predictors of the outcome variables. Results The overall response rate at the end line was 92.9%. Thus, compared to that in controls, the PPD in the intervention clusters was considerably lower (20 (7.6%) vs. 74 (28.9%)), P = 0.001)/65% (AOR = 0.35, 95% CI = 0.13–0.99), although no difference was detected at baseline. Social support (AOR = 0.04, 95% CI = 0.01–0.15), partner emotional support (AOR = 0.24, 95% CI = 0.12–0.51), PPD literacy (AOR = 0.25, 95% CI = 0.11–0.62), and self-esteem (AOR = 0.22, 95% CI = 0.11–0.47) were more likely to protect mothers from PPD. On the contrary, domestic work (AOR = 9.75, 95% CI = 3.37–28.16), neonates with complications (AOR = 5.79, 95% CI = 2.04–16.45), and unhealthy coping (AOR = 2.39, 95% CI = 1.06–5.42) exposed mothers to PPD. Conclusion The implementation of a PGBPE in primary healthcare units (PHCUs) was effective at preventing PPD. Therefore, this intervention method has to be promoted and used in PHCUs to prevent PPD. Clinical Trial Registration [Pan African Clinical Trial Registry], identifier [PACTR 202203616584913].